MEN’S INVOLVEMENT IN CARE AND SUPPORT OF WOMEN DURING PREGNANCY AND CHILDBIRTH AMONG MOTHERS ATTENDING ANTENATAL CARE AT ENTEBBE REGIONAL REFERRAL HOSPITAL. A CROSS-SECTIONAL STUDY. - Nalwanga, Lilian; Mpamize, Habert; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2025)
Background Men are involved in support of women during pregnancy and childbirth, as men participate in decisions and activities that will improve women’s and child health outcomes. Therefore, this study aimed to assess men’s involvement in the care and support of women during pregnancy and childbirth among mothers attending antenatal care at Entebbe Regional Referral Hospital. Methodology A descriptive cross-sectional study design was employed to select 40 mothers. A simple random sampling method was used, and data was collected using a semi-structured researcher-administered questionnaire with both open and close-ended questions. Microsoft Excel was used for data analysis. Results This study revealed that 65% of the respondents’ husbands had a monthly income of between 100000-300000 Uganda shillings, Half of the husbands to the respondents always provided transport costs to the health facility, and 52% of the husbands never had time to escort their wives for ANC. The findings of the current study indicated that 70% of the respondents agreed that the health workers encouraged men to escort their wives to ANC. However, 37.5% of the respondents believed men were not motivated to attend ANC. 85% of the participants reported having no cultural norms that ban men from accessing labor wards and ANC. However, 50% believed it is the responsibility of the in-laws to care for the woman during childbirth. In conclusion Increasing men’s involvement in maternal care requires a multi-faceted approach that addresses financial, cultural, and health facility-related barriers. By creating a more inclusive and supportive environment for men, both at home and within healthcare settings, maternal and child health outcomes can be significantly improved. Recommendation Health facilities should be more couple-friendly by offering services that encourage male involvement, such as priority service for couples attending ANC together and promoting couple-specific health education.